Factors Contributing to the Failure of Environmental Governance in Waste Management at the Regional Level - Shabarudin, Shabarudin; Husni Thamrin (Universitas Kuningan, 2025)
The purpose of this study is to analyze the Implementation of Environmental Governance Policy at the Parit Enam Final Disposal Site in Pangkalpinang and the Factors Contributing to the Failure in Preventing Open Dumping Practices. An empirical approach was used to identify a significant gap between the established waste management policy and its implementation in the field. The methodology combined policy document analysis, field observation, environmental parameter measurement, and in-depth interviews with stakeholders. The results showed that the Implementation of Environmental Governance Policy at the Parit Enam Final Disposal Site in Pangkalpinang was regulated by the law on waste management, government regulations on household waste management, and Pangkalpinang City Regulation on Waste Management. Although the implementation is underway, some obstacles remain. The factors contributing to the failure in preventing open dumping practices originated from a limited operational budget and management infrastructure, weak coordination between related institutions, a low technical capacity among managers, and minimal community participation in waste management. In conclusion, the final disposal site has a significant impact on the quality of groundwater, air, and soil, exceeding environmental quality standards. Leachate contamination was detected in the wells of residents within a 1 km radius of the location. This study recommends improvement in governance through evidence-based policy reform, increased infrastructure budget allocation, technical capacity development, and a participatory approach in an integrated waste management system to address the problem of open dumping at the Parit Enam Final Disposal Site in Pangkalpinang.